Предмет: Алгебра,
автор: Аноним
2)(a + 2) (n - m);
5) (a + 2) (6-3);
8) (k - 6) (7 - d).
3) (t + s) (b + k);
6) (4-6) (5 + c);
Ответы
Автор ответа:
0
2)(a + 2) (n - m)=an-ma+2n-2m
5) (a + 2) (6-3)=6a-3a+12-6=3a+6
8) (k - 6) (7 - d)=7k-dk-42+6d
3) (t + s) (b + k)=tb+kt+sb+sk
6) (4-6) (5 + c)=20+4c-30-6c= -2c-10
(4-6) (5 + c)= -2(5+c)= -2c-10
Похожие вопросы
Предмет: Русский язык,
автор: mihajlova31
Предмет: Английский язык,
автор: ИлонааШ
Предмет: Русский язык,
автор: данила1704
Предмет: Информатика,
автор: заучка17
Предмет: Алгебра,
автор: khalmatova2003